Gender Compositions in Executive Management Teams and their Impact on Firm Peformance - Sridhar Arcot; Stefan Gröschl (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
This paper examines gender composition in executive management teams and explores how female executive managers affect the financial performance of their organizations. Using data compiled from 2,872 US companies between 1992 and 2008, we find evidence of a significant non-linear relationship between the proportion of female executives in a firm and its financial performance. We show that this relationship is present only in firms with entrepreneurial organizational characteristics (i.e., firms that are simple, small, young, and risky). By demonstrating the importance of these moderating characteristics, we extend Van Knippenberg, De Dreu and Homan's (2004) integrative theoretical model of social categorization and elaboration processes. The findings of this paper also contribute to critical mass research, and affect policy makers concerned with gender quotas in various institutional and business contexts.
Keywords: 650; CEM; female executive management